HgrA is necessary and sufficient to drive hyphal growth in the dimorphic pathogen Penicillium marneffei. Issue 5 (9th May 2013) - Bugeja, Hayley E.; Hynes, Michael J.; Andrianopoulos, Alex
Summary: Fungi produce multiple morphological forms as part of developmental programs or in response to changing, often stressful, environmental conditions. An opportunistic pathogen of humans, Penicillium marneffei displays multicellular hyphal growth and asexual development (conidiation) in the environment at 25°C and unicellular yeast growth in macrophages at 37°C. We characterized the transcription factor, hgrA, which contains a C2 H2 DNA binding domain closely related to that of the stress‐response regulators Msn2/4 of Saccharomyces cerevisiae . Northern hybridization analysis demonstrated that hgrA expression is specific to hyphal growth, and its constitutive overexpression prevents conidiation and yeast growth, even in the presence of inductive cues, and causes apical hyperbranching during hyphal growth. Consistent with its expression pattern, deletion of hgrA causes defects in hyphal morphogenesis and the dimorphic transition from yeast cells to hyphae. Specifically, loss of HgrA causes cell wall defects, reduced expression of cell wall biosynthetic enzymes and increased sensitvity to cell wall, oxidative, but not osmotic stress agents. These data suggest that HgrA does not have a direct role in the response to stress but is an inducer of the hyphal growth program and its activity must be downregulated to allow alternative developmental programs, including the morphogenesis of yeast cells in macrophages.